P1296CARDIAC COMPLICATIONS OF ARTERIOVENOUS FISTULAS IN PATIENTS WITH END-STAGE RENAL DISEASE. (6th June 2020) - Breik, Nessrine; Jbeli, Hela; Fattoum, Safa; Ouertani, Imen; Ben kaab, Badreddine; Mami, Ikram; Ben Fatma, Lilia; Beji, Soumaya; Smaoui, Wided; Benhmida, Fethi; Rais, Lamia; Zouaghi, Mohammed Karim
Abstract: Background and Aims: Current literature suggests the arteriovenous fistula (AVF) to be the preferred type of vascular access for hemodialysis. However, AVFs have significant and potentially deleterious effects on cardiac functions particularly in the setting of preexisting heart disease. The aim of this study is to compare the clinical and echocardiographic evolution after creation of a proximal AVF and a radial AVF. Method: We conducted a retrospective descriptive study including all chronic hemodialysis patients through AVF. Group 1 (G1) included patients with proximal AVF and group 2 (G2) patients with radial AVF. Results: Twenty-four patients were collected in G1 and the average age was 55 years. G2 included 13 patients with a mean age of 44 years. Systolic blood pressure decreased after AVF creation in both groups (G1: 62.5%, G2: 45%, NS). A dyspnea was noted in 70% of cases of G1 and 38.4% of cases of G2 (NS). The interventricular septum was thickened in 20.8% of cases of G1 and 38.4% of G2 (NS). Left ventricular (LV) dilatation was observed in both groups with LV diastolic telegram diameter increase of 58% in G1 versus 10% in G2 (p = 0.04). A decrease in LV ejection fraction was found in 62.5% in G1 and 46.1% in G2 (p = 0.066). The major cardiac complications in G1 were acute coronary syndrome in 5 patients and atrial fibrillation in 4 cases after an average of 60 months and 35 months, respectively. No cardiac complications were noted in G2. Conclusion: AVFs remain the preferred type of vascular access for chronic hemodialysis therapy because they are associated with better long-term patency and fewer complications compared with synthetic grafts. Its seat will depend on the vascular state and the cardiac status of the dialysis patient.